Generation of three human induced pluripotent stem cell sublines (MZT04D, MZT04J, MZT04C) for reproductive science research - Erica C. Pandolfi; Ernesto J. Rojas; Enrique Sosa; Joanna J. Gell; Timothy J. Hunt; Sierra Goldsmith; Yuting Fan; Sherman J. Silber; Amander T. Clark (Stem Cell Research, 2019)
We generated three human induced pluripotent stem cell (hiPSC) sublines from human dermal fibroblasts (HDFs) (MZT04) generated from a skin biopsy donated from a previously fertile woman. The skin biopsy was broadly consented for generating hiPSC lines for biomedical research, including unique consent specifically for studying human fertility, infertility and germ cells. hiPSCs were reprogrammed using Sendai virus vectors and were subsequently positive for markers of self-renewal including OCT4, NANOG, TRA-1-81 and SSEA-4. Pluripotency was further verified using teratomas and PluriTest. These sublines serve as controls for hiPSC research projects aimed at understanding the cell and molecular regulation of female fertility and infertility.